2011
DOI: 10.5114/aoms.2011.23410
|View full text |Cite
|
Sign up to set email alerts
|

Plasma asymmetric dimethylarginine predicts restenosis after coronary angioplasty

Abstract: IntroductionAsymmetric dimethylarginine (ADMA) is an endogenous competitive inhibitor of endothelial nitric oxide synthase. Asymmetric dimethylarginine may influence the process of restenosis after coronary angioplasty. The aim of the study was to determine if initial plasma ADMA level could predict restenosis after coronary angioplasty and stenting.Material and methodsThe study group consisted of 60 consecutive patients (10 women and 50 men, average age 58.9 ±10.4 years old), who underwent percutaneous corona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…In a prospective study done by Derkacz et al (9) it has been demonstrated that pre-procedural elevated plasma ADMA levels increased the risk of restenosis in patients who underwent coronary angioplasty and stenting with bare metal stents. In our study we did not analyzed the plasma ADMA levels before stenting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a prospective study done by Derkacz et al (9) it has been demonstrated that pre-procedural elevated plasma ADMA levels increased the risk of restenosis in patients who underwent coronary angioplasty and stenting with bare metal stents. In our study we did not analyzed the plasma ADMA levels before stenting.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years few studies reveal a link between ADMA and stent restenosis due to its role on NO formation (9-11). Derkacz et al (9) concluded that pre-procedural elevated plasma ADMA levels increases the risk of restenosis in patients who underwent coronary angioplasty and stenting with bare metal stents. Khalifa et al (10) found that the patients who developed stent restenosis had an increase in ADMA levels following coronary stenting.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that statins upregulate both PCSK9 mRNA levels and LDLR via activation of sterol-mediated SREBP-2, an important activator of DDAH transcription and activity 48 . Since reduced DDAH activity is linked to endothelial dysfunction, we speculate that statin therapy might decrease ADMA levels through multiple mechanisms such as activation of sterol-mediated SREBP-2, increasing of transcription of PCSK9 or by decreasing ADMA-induced inflammatory reaction, modulated by MAPK 49,50 . This meta-analysis has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, by increasing VSMC proliferation and extracellular matrix formation, it may also influence the process of ISR (ref. 20,21 ). Previous reports showed an association between ISR and vasodilator dysfunction in forearm resistance vessels 18,21,22 , and several small studies have reported an association between ISR and increased plasma ADMA levels 17,18,20 .…”
Section: Matrix Metalloproteinases (Mmps) Comprise a Family Of Zinc-dmentioning
confidence: 99%